2014
DOI: 10.1159/000366445
|View full text |Cite
|
Sign up to set email alerts
|

Periodontal Disease, Renal Dysfunction and Heightened Leukocytosis

Abstract: Background: Leukocytosis is a powerful predictor of incident chronic kidney disease (CKD) and related outcomes. However, the association between periodontitis measures and increased leukocytosis in the context of CKD has not been well described. We sought to identify which individual measures of periodontal disease may best associate with reduced estimated glomerular filtration rate (eGFR) and albuminuria, and to test if these measures were associated with increased leukocytosis in subjects with established CK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 46 publications
1
19
0
Order By: Relevance
“…This 4‐year longitudinal study of community‐dwelling older men and women found CKD was associated with a greater risk of AL progression. This finding supported previous cross‐sectional studies showing an association between CKD and periodontal disease …”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This 4‐year longitudinal study of community‐dwelling older men and women found CKD was associated with a greater risk of AL progression. This finding supported previous cross‐sectional studies showing an association between CKD and periodontal disease …”
Section: Discussionsupporting
confidence: 93%
“…The principal exposure was the presence or absence of CKD, defined as an eGFR of <60 mL/min/1.73 m 2 . eGFR was calculated by using the abbreviated Modification of Diet in Renal Disease Study equation, with a Japanese coefficient of 0.881: eGFR (mL/min/1.73 m 2 ) = 0.881 × 186.3 × Age −0.203 × Serum‐creatinine −1.154 (if female × 0.742).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…ORs (95% CI) assessing the association between periodontitis and CKD were considered (Figure ). Eight studies (Fisher & Taylor, ; Fisher, Taylor, Papapanou, Rahman, & Debanne, ; Fisher, Taylor, West, & McCarthy, ; Fisher, Taylor, Shelton, et al., ; Ioannidou, Hall, Swede, & Himmelfarb, ; Ioannidou & Swede, ; Ioannidou, Swede, & Dongari‐Bagtzoglou, ; Salimi, Ng, Seliger, & Parsa, ) were based on the NHANES III cohort, two studies on the D‐ARIC study (Grubbs et al., ; Kshirsagar et al., ), and two on Yokogoshi study (Yoshihara et al., , ). Therefore, only the study presenting the largest population sample in each subanalysis was pooled in this meta‐analysis.…”
Section: Resultsmentioning
confidence: 99%
“…[29] Albuminuria has been shown to be related with periodontal disease. [30] A previous report showed that decreased kidney function (characterized by low eGFR) may be associated with periodontitis. [24] International recommendations suggest that the measurement of serum creatinine should be supplemented with eGFR using the MDRD study's equation.…”
Section: Discussionmentioning
confidence: 99%